ENVIRONMENTAL POLLUTION AND HEALTH HAZARDS : AN AWARENESS STUDY IN THE REPRODUCTIVE AGE BRACKETS - Patro, Lingaraj (IJRDO -JOURNAL OF HEALTH SCIENCES AND NURSING, 2017)
The purpose of the study is to understand the sensitivity of adult groups toenvironmental pollution. The project was carried out by collecting information from therespondents of reproductive age groups using structured interview schedules. The interviewschedule was pretested by a pilot study and necessary modifications were done. The data wereassigned with percentage scores for a quantitative analysis. The awareness level was evaluatedfrom the stand points of air, water, soil, noise, radiation and thermal pollution. The responseswere compiled and interpreted from the objective point of view. The results revealed that amongthe pollution categories most of the samples were mostly aware of air, water, soil and noisepollution and very few knew about thermal and radiation pollution. Table-1 depicts awarenesslevel of samples with regard to environmental pollution. Information shows that a great numberof samples (85 %) were aware of air and water pollution, 80 % of samples were aware of soil andnoise pollution, 60% of samples were aware of thermal pollution and only 50 % samples wereaware of radiation pollution. Table -2. Reveals that 25 % of the samples were aware of sourcesof soil pollution and noise pollution, similarly 20 % of the samples were aware of sources of airpollution, water pollution and thermal pollution and only 15 % of the samples were aware ofsources of radiation pollution. Table- 3 shows that most of the samples (25 %) were aware ofpollutants of soil pollution, 20 % of the samples were aware of pollutants of air pollution, waterpollution, noise pollution, radiation pollution and thermal pollution. Table-4 reveals that 20 % ofthe samples were aware of ill health effects due to water pollution, noise pollution and thermalpollution 15 % of the samples were aware of ill health effects due to air pollution and 10 % ofthe samples were aware of ill health effects due to soil pollution and radiation pollution. Thus,proper strategies for environmental education and legislation should be enforced.